Effects of combined endurance and strength training on left ventricular morphology in male and female rowers - Haykowsky, M.; Chan, S.; Bhambhani, Y.; Syrotuik, S.; Quinney, H.; Bell, G. (Canadian Journal of Cardiology, 1998)
The effects of 10 weeks of combined endurance and strength training on left ventricular (LV) morphology, muscular strength, maximal oxygen consumption (VO2max) and rowing performance were assessed. Twenty-five subjects (eight males, mean age 23.0±6.1 years, and 17 females, 22.7±5.0 years) were tested at baseline and after five and 10 weeks of training. Combined training was associated with significant improvements in VO2max, rowing performance and muscular strength after 10 weeks of training. A significant increase in LV diastolic dimension was found in males after 10 weeks of training; however, no significant alteration was found for any other measured echocardiographic variable. Therefore, with the exception of LV diastolic dimension in males, 10 weeks of combined endurance and strength training appears to be an insufficient stimulus to elicit significant alterations in LV morphology despite changes in VO2max, muscular strength or rowing performance.